Antimicrobial susceptibility, serotype distribution, virulence profile and molecular typing of piliated clinical isolates of pneumococci from east coast, Peninsular Malaysia - Dzaraly, Nurul Diana; Mohd Desa, Mohd Nasir; Muthanna, Abdul Rahman; Masri, Siti Norbaya; Mohd Taib, Niazlin; Suhaili, Zarizal; Sulaiman, Nurshahira; Zainal Baharin, Nurul Hana; Cheah, Yun Shuan; Ariffin, Zarina; A. Rahman, Nor Iza; Mohd Rani, Farahiyah; et al. (Nature Research, 2021)
Pilus has been recently associated with pneumococcal pathogenesis in humans. The information regarding piliated isolates in Malaysia is scarce, especially in the less developed states on the east coast of Peninsular Malaysia. Therefore, we studied the characteristics of pneumococci, including the piliated isolates, in relation to antimicrobial susceptibility, serotypes, and genotypes at a major tertiary hospital on the east coast of Peninsular Malaysia. A total of 100 clinical isolates collected between September 2017 and December 2019 were subjected to serotyping, antimicrobial susceptibility test, and detection of pneumococcal virulence and pilus genes. Multilocus sequence typing (MLST) and phylogenetic analysis were performed only for piliated strains. The most frequent serotypes were 14 (17%), 6A/B (16%), 23F (12%), 19A (11%), and 19F (11%). The majority of isolates were resistant to erythromycin (42%), tetracycline (37%), and trimethoprim-sulfamethoxazole (24%). Piliated isolates occurred in a proportion of 19%; 47.3% of them were multidrug-resistant (MDR) and a majority had serotype 19F. This study showed ST236 was the most predominant sequence type (ST) among piliated isolates, which was related to PMEN clone Taiwan19F-14 (CC271). In the phylogenetic analysis, the piliated isolates were grouped into three major clades supported with 100% bootstrap values. Most piliated isolates belonged to internationally disseminated clones of S. pneumoniae, but pneumococcal conjugate vaccines (PCVs) have the potential to control them.